Ocular Chlamydia trachomatis infection, anti-Pgp3 antibodies and conjunctival scarring in Vanuatu and Tarawa, Kiribati before antibiotic treatment for trachoma. Issue 4 (April 2020) - Butcher, Robert; Handley, Becca; Garae, Mackline; Taoaba, Raebwebwe; Pickering, Harry; Bong, Annie; Sokana, Oliver; Burton, Matthew J; Sepúlveda, Nuno; Cama, Ana; Mesurier, Richard Le; Solomon, Anthony W.; et al.
Highlights: In Vanuatu, ocular Chlamydia infection prevalence is low; in Kiribati it is high. In Vanuatu, Pgp3 seroprevalence does not increase in childhood; in Kiribati it does. Conjunctival scarring is more common in adults in Kiribati than in Vanuatu. Trachomatous inflammation—follicular lacks specificity for ocular Chlamydia infection. Non-TF markers may help to determine need for interventions against active trachoma. Abstract: Introduction: In the peri-elimination setting, the positive predictive value of trachomatous inflammation–follicular (TF), the primary marker used to determine need for antibiotics for trachoma, is suboptimal. Here, three non-TF measures are used to compare two regions where TF prevalence exceeds the threshold for intervention, but where the Chlamydia trachomatis ( Ct ) prevalence is different. Methods: Population prevalence of trachoma was measured in Vanuatu ( n = 3470) and Kiribati ( n = 2922). Dried blood spots (DBS) and conjunctival photographs were collected from every survey participant, and conjunctival swabs were collected from those aged 1–9 years. Individuals were tested for blood anti-Pgp3 antibodies, Ct DNA at the conjunctiva and severity of conjunctival scarring. Results: The prevalence of TF in 1–9-year-olds was 16.5% in Vanuatu and 38.2% in Tarawa. 7% of people aged ≥1 year in Vanuatu had conjunctival scarring compared to 27% in Tarawa. The prevalence of ocular Ct infection in 1–9-year-olds was 1.5% in Vanuatu and 27.4% in Tarawa. The seroconversion rate amongst 1–9-year-old children in Vanuatu and Tarawa was 0.018 and 0.197 events per child per year, respectively. Conclusions: Comparing Vanuatu to Tarawa demonstrates several markers that could be used to differentiate the trachoma status of populations in these (and other) locations.